2002
DOI: 10.1113/jphysiol.2001.016394
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine inhibition via A1 receptor of N-type Ca2+ current and peptide release from isolated neurohypophysial terminals of the rat

Abstract: ). The modulation by ATP of pre-synaptic ion channels (Zimmermann, 1994) via specific purinergic receptors, for example, could result in changes in subsequent release of neurotransmitters from the pre-synaptic site and, as a consequence, on the functional effect at the post-synaptic site.ATP is rapidly hydrolysed by ecto-nucleotidases (Gordon et al. 1989) even at pre-synaptic sites (Thirion et al. 1996) to adenosine 5‚-diphosphate (ADP), adenosine 5‚-monophosphate (AMP) and adenosine. Adenosine, the final hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…2B) each had a mean stimulated AVP release of 195.04 pg ± 1.22 pg. Such close similarities in total peptide release between individual collection lines, following high potassium depolarization, has consistently been observed in our lab (see, e.g., Wang et al, 1997, 1999, 2002). In this way, if there was no effect on the second filter from secretion from the first filter, then the total peptide secreted (both filters) should be twice the peptide secreted from just one filter alone.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…2B) each had a mean stimulated AVP release of 195.04 pg ± 1.22 pg. Such close similarities in total peptide release between individual collection lines, following high potassium depolarization, has consistently been observed in our lab (see, e.g., Wang et al, 1997, 1999, 2002). In this way, if there was no effect on the second filter from secretion from the first filter, then the total peptide secreted (both filters) should be twice the peptide secreted from just one filter alone.…”
Section: Resultssupporting
confidence: 86%
“…Since the biophysical properties of ion channels alone cannot explain the HNS interburst characteristics (Lemos and Wang, 2000), we hypothesize that the release of ATP is a mechanism underlying release efficacy in the NHT. Its presence would enhance the release of AVP from the neurohypophysis early during the bursting pattern followed by a subsequent build up of adenosine, metabolized from ATP, which would inhibit release by inhibiting the N‐type (Wang et al, 2002) calcium current via the A 1 receptor (Knott et al, 2007). Furthermore, since ATP is stored at high concentrations in most secretory vesicles and has been shown to be released from chromaffin cells and many neurons (Zimmermann, 1994), we postulate that the release of ATP is important in modulating release from other, if not all, bursting nervous system terminals.…”
Section: Discussionmentioning
confidence: 99%
“…The imperative motor factor of sleep (i.e., adenosine) strongly inhibits oxytocin release (Wang et al, 2002) and can be classified as an attachment termination factor (Table 1) 23 . The interaction between ghrelin (i.e., the imperative motor factor of hunger) and oxytocin is at present a topic of (neuro)endocrinological research.…”
Section: The Interaction Between Oxytocin and Imperative Motor Factorsmentioning
confidence: 99%
“…We have previously shown that ATP, acting via P2X receptors, potentiates only AVP release from HNS terminals (4), whereas its metabolite adenosine, via A1 receptors acting on transient Ca 2+ currents, inhibits both AVP and OT secretion (5). We have shown that exogenous ATP induces inward currents (6) and causes the release of only vasopressin (AVP) from neurohypophysial terminals (4); both effects are inhibited by suramin and pyridoxal‐phosphate‐6‐azophenyl‐2′,4′‐disulfonic acid (PPADS), selective but not specific, P2X2 and P2X3 receptor antagonists.…”
mentioning
confidence: 99%